Design, Synthesis and Evaluation of Branched RRWQWR-Based Peptides as Antibacterial Agents Against Clinically Relevant Gram-Positive and Gram-Negative Pathogens - Vega, Sandra C.; Martínez, Diana A.; Chalá, María del S.; Vargas, Hernán A.; Rosas, Jaiver E. (Frontiers in Microbiology, 2018)
Multidrug resistance of pathogenic bacteria has become a public health crisis that requires the urgent design of new antibacterial drugs such as antimicrobial peptides (AMPs). Seeking to obtain new, lactoferricin B (LfcinB)-based synthetic peptides as viable early-stage candidates for future development as AMPs against clinically relevant bacteria, we designed, synthesized and screened three new cationic peptides derived from bovine LfcinB. These peptides contain at least one RRWQWR motif and differ by the copy number (monomeric, dimeric or tetrameric) and structure (linear or branched) of this motif. They comprise a linear palindromic peptide (RWQWRWQWR), a dimeric peptide (RRWQWR)2KAhxC and a tetrameric peptide (RRWQWR)4K2Ahx2C2. They were screened for antibacterial activity against Enterococcus faecalis (ATCC 29212 and ATCC 51575 strains), Pseudomonas aeruginosa (ATCC 10145 and ATCC 27853 strains) and clinical isolates of two Gram-positive bacteria (Enterococcus faecium and Staphylococcus aureus) and two Gram-negative bacteria (Klebsiella pneumoniae and Pseudomonas aeruginosa). All three peptides exhibited greater activity than did the reference peptide, LfcinB (17-31), which contains a single linear RRWQWR motif. Against the ATCC reference strains, the three new peptides exhibited minimum inhibitory concentration (MIC50) values of 3.1-198.0 μM and minimum bactericidal concentration (MBC) values of 25-200 μM, and against the clinical isolates, MIC50 values of 1.6-75.0 μM and MBC values of 12.5-100 μM. However, the tetrameric peptide was also found to be strongly hemolytic (49.1% at 100 μM). Scanning Electron Microscopy (SEM) demonstrated that in the dimeric and tetrameric peptides, the RRWQWR motif is exposed to the pathogen surface. Our results may inform the design of new, RRWQWR-based AMPs.